Analysis of line intensity ratio for optical transitions of 3d6 levels and plasma screening effect on atomic structure of Fe III ion. (May 2023) - Yadav, Falta; Goyal, Arun; Singh, Narendra
Abstract: Iron emission lines are observed from most classes of astronomical objects through a wide spectral range from infrared to X-ray. For a useful analysis of these lines, accurate atomic data for neutral iron and its ions is required. In this work, we have done calculations of energy levels and radiative data of Fe III by using the relativistic configuration interaction method with the implementation of the flexible atomic code (FAC). We have calculated emission-line intensity ratios for optical transitions among the fine-structure levels of the 3d 6 configuration at temperature 10 4 K and density n e = 10 4 c m − 3 . We have also compared our results with the observed spectra of Herbig-Haro objects HH 202 of Orion Nebula, Planetary Nebula, and NGC 2392, post-asymptotic giant branch star (PAGB) HD341617. We have also discussed various discrepancies between the observed spectra from these nebulae and our calculations. The atomic structure of plasma-embedded Fe III is also analyzed using flexible atomic code (FAC). The graphical study shows that transition wavelengths, oscillator strengths, and transition rates are very sensitive to the plasma environment in the density range 10 21 c m − 3 to 5 × 10 22 c m − 3 and spectral lines associated to Δn = 0 transitions for Fe III ion are blueshifted. We have also studied the dependence of emission line intensity ratios on plasma density and temperature. We believe that our presented results are useful in spectroscopic analysis and examination of astrophysical and laboratory plasma. Highlights: Fine structure energy levels of 3d 6 configuration of Fe III ion is presented. Radiative data M1 transitions within 3d 6 levels for Fe III are provided. Line intensity ratios for optical transitions compared with Orion Nebula, Planetary Nebula and PAGB. Plasma screening effect on energy levels and transition data for Fe III are analyzed.